2017
DOI: 10.15253/2175-6783.2016000600012
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk and stress in employees of a higher education institution

Abstract: Objective: to analyze the association between high levels of stress and the frequency of cardiovascular risk factors in employees of a higher education institution. Methods: this is a cross-sectional study with 201 employees of a university. A form containing socioeconomic data, the International Physical Activity Questionnaire (short version), the Alcohol Use Disorders Identification Test and the Work Stress Scale were used for data collection. Data analysis was performed using the probability ratio and One-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The difficulties in recruiting more workers were simply based on our staffing limitations. However, the sample under study is larger when compared to other studies with a broader focus on health problems in HEIs, as can be observed in the Saudi Arabia, Spain, and Brazil studies (322 participants vs. 233, 124, and 201, respectively) [ 9 , 10 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…The difficulties in recruiting more workers were simply based on our staffing limitations. However, the sample under study is larger when compared to other studies with a broader focus on health problems in HEIs, as can be observed in the Saudi Arabia, Spain, and Brazil studies (322 participants vs. 233, 124, and 201, respectively) [ 9 , 10 , 73 ].…”
Section: Discussionmentioning
confidence: 99%